Gray, J. (2010). Show sold separately. Promos, spoilers and other media paratexts. - Yáñez, Brenda Azucena Muñoz (Departamento de Psicología y Comunicación de Texas A&M International University | Facultad de Trabajo Social y Desarrollo Humano de la Universidad Autónoma de Nuevo León, 2014)
Reseña del libro: Gray, J. (2010). Show sold separately. Promos, spoilers and other media paratexts. New York: New York University Press.